1979
DOI: 10.3758/bf03213823
|View full text |Cite
|
Sign up to set email alerts
|

Some effects of later-occurring information on the perception of stop consonant and semivowel

Abstract: In three experiments, we determined how perception of the syllable-initial distinction between the stop consonant [b] and the semivowel [w], when cued by duration of formant transitions, is affected by parts of the sound pattern that occur later in time. For the first experiment, we constructed four series of syllables, similar in that each had initial formant transitions ranging from one short enough for [ba] to one long enough for [wa], but different in overall syllable duration. The consequence in percept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
332
6
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 283 publications
(362 citation statements)
references
References 30 publications
23
332
6
1
Order By: Relevance
“…Previous results mainly indicated that the perception of the identity of a segment is affected by its adjacent segments (Lindblom & Studdert-Kennedy, 1967;Mann, 1980;Mann & Repp, 1981;Miller & Liberman, 1979;Gaskell & Marslen-Wilson, 1996). Our present results add a new twist to such context effects by showing that adjacent segments also influence the perception of the presence of a segment (see Repp, 1983;Repp et al, 1978, for similar effects).…”
Section: Discussionsupporting
confidence: 79%
“…Previous results mainly indicated that the perception of the identity of a segment is affected by its adjacent segments (Lindblom & Studdert-Kennedy, 1967;Mann, 1980;Mann & Repp, 1981;Miller & Liberman, 1979;Gaskell & Marslen-Wilson, 1996). Our present results add a new twist to such context effects by showing that adjacent segments also influence the perception of the presence of a segment (see Repp, 1983;Repp et al, 1978, for similar effects).…”
Section: Discussionsupporting
confidence: 79%
“…Some effects are to a greater or lesser degree indirect. Thus the rate of speech implied by just a single long or short vowel can influence decisions about the identity of an immediately preceding consonant (Miller and Liberman, 1979), a photograph of a person can suffice to cue the relevant talker characteristics (Hay, Warren and Drager, 2006), and exposure to a dialect label can bias the recall of the nature of a vowel sound (Hay, Nolan and Drager, 2006). Combined use of very different information sources -acoustics of the signal, stored knowledge in the lexicon or general knowledge in memory, abstract labels and prior episodes of cognitive or sensory processing -in an integrated fashion is however no problem for a system such as that proposed by the Merge model.…”
Section: Categorical Decision-makingmentioning
confidence: 99%
“…These adaptation processes can take place very rapidly. For example, adaptation to natural changes in speech rate (e.g., J. L. Miller, 1981;J. L. Miller & Lieberman, 1979;Summerfield, 1981) or to changes in the spectral characteristics of the communication channel (Ladefoged & Broadbent, 1957;Summerfield, Haggard, Foster, & Gray, 1984;Watkins, 1991) occur in less than a second.…”
mentioning
confidence: 99%